The paradigm of the war on crime: Legitimating inhuman treatment? - Delmas-Marty, Mireille (Journal of international criminal justice, 2007)
Since 11 September 2001, a new paradigm has developed in criminal law. Parallel to the idea of the war on terror, a paradigm based around war on crime has emerged. Inevitably, however, a paradigm of war leads to abandoning scientific approaches based on a legal-moral vision (crime, guilt and punishment) in favour of a merely pragmatic vision, which associates national security with social defence. Based on an unclear concept of dangerousness, presumed by simple membership in a group labeled enemy , the goal is to neutralize, or even eliminate, the criminal/deviant. When combined with a denial of international protections, deconstructing national criminal law thus runs the risk of pushing a black hole through the rule of law. Many have criticized such a paradigm; however, the author points out that the paradigm of the war on crime (and more generally the war on terror), provided that it respects international law, can be useful, because it shows the need to overcome the binary opposition between war and peace, as well as between war crimes and ordinary crimes. Nonetheless, it must be clear that this paradigm can only be one of transition. To overcome the war peace dichotomy in a global community and to reconstruct the relationship between terrorism and torture, neither a war crimes nor a war on crime paradigm is truly sufficient. Only through the amplification of a paradigm of crime against humanity (itself unstable and evolving but free from the war metaphor) can we reconstruct humanity as a value and make it the cornerstone of any legal system